2019
DOI: 10.1039/c9tc04980k
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Ising chains in frustrated LnODCO3: the influence of magnetic structure in magnetocaloric frameworks

Abstract: Understanding how to tune magnetic interactions to optimise the magnetocaloric effect is crucial for designing more efficient solid state refrigerants; this work probes this relationship for the promising LnODCO3 phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 34 publications
5
23
0
Order By: Relevance
“…8,33 We have previously established the magnetic states that form in both Tb(HCO 2 ) 3 and TbOHCO 3 in the absence of applied magnetic fields. 9,35 Tb(HCO 2 ) 3 , which adopts R3m rhombohedral symmetry at all measured temperatures, 36 shows strong diffuse scattering indicative of short range order below 20 K, where its magnetocaloric effect begins to be significant. This short range order is formed of ferromagnetically coupled linear chains of Isinglike moments aligned along the c-axis, antiferromagnetically coupled in a triangular array within the ab plane.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…8,33 We have previously established the magnetic states that form in both Tb(HCO 2 ) 3 and TbOHCO 3 in the absence of applied magnetic fields. 9,35 Tb(HCO 2 ) 3 , which adopts R3m rhombohedral symmetry at all measured temperatures, 36 shows strong diffuse scattering indicative of short range order below 20 K, where its magnetocaloric effect begins to be significant. This short range order is formed of ferromagnetically coupled linear chains of Isinglike moments aligned along the c-axis, antiferromagnetically coupled in a triangular array within the ab plane.…”
Section: Introductionmentioning
confidence: 87%
“…It has previously been shown that Tb(HCO 2 ) 3 and TbOHCO 3 undergo transitions to the TIA phase at B1.6 K and an antiferromagnetic state at B1.2 K, respectively. 9,36,43 Above their ordering temperatures these materials both contain short range ferromagnetic Ising chains in the correlated paramagnetic phase, asserted to be responsible for their highly efficient magnetocaloric effects. 8,9 Variable field measurements above and below these transitions show features suggestive of the ordering behaviour.…”
Section: Magnetic Property Measurementsmentioning
confidence: 99%
See 3 more Smart Citations